A New Claims-Based Unemployment Dataset: Application to Postwar Recoveries Across U.S. States - Andrew Fieldhouse; Sean Howard; Christoffer Koch; David Munro (Global Labor Organization (GLO), 2022)
Using newly digitized unemployment insurance claims data we construct a historical monthly unemployment series for U.S. states going back to January 1947. The constructed series are highly correlated with the Bureau of Labor Statics' state-level unemployment data, which are only available from January 1976 onwards, and capture consistent patterns in the business cycle. We use our claims-based unemployment series to examine the evolving pace of post-war unemployment recoveries at the state level. We find that faster recoveries are associated with greater heterogeneity in the recovery rate of unemployment and slower recoveries tend to be more uniformly paced across states. In addition, we find that the pace of unemployment recoveries is strongly correlated with a states' manufacturing share of output.
Keywords: C82; E24; E32; J64; J65; R11; 330; State-Level Unemployment Rates; Unemployment Insurance; Economic Recoveries; Regional Business Cycles